Nigerian Female Filmmakers’ Representation of Men in Nollywood Films (Journal of Management and Social Sciences, 2025)
This paper examines how contemporary female auteurs in Nollywood are challenging traditional portrayals of women, reconstructing their persona in ways that defy patriarchal norms and reflect more complex, multifaceted identities. Historically, Nollywood films have often depicted women through stereotypical roles—such as submissive wives, femme fatales, or caregivers—reinforcing societal expectations of gender. However, a new generation of women filmmakers are re-narrativising these conjectures, presenting women as empowered, independent, and capable of navigating societal, economic, and political landscapes on their own terms. Five films written, produced, and directed by prominent Nigerian female auteurs were purposively selected based on their thematic relevance. They are: Omoni Oboli's (2016) Wives on Strike, Kemi Adetiba's (2018) King of Boys, Funke Akindele's (2019) and Your Excellency (2020) Omo Ghetto the Saga, and Biodun Stephen's (2017) Tiwa's Baggage. Findings show that these auteurs deconstructed patriarchal tropes and portrayed women in a diverse range of empowered roles in ways that resonate with contemporary Western feminist movements and they reflect the evolving status of Nigerian women. However, very little attention is paid to creating identities for male characters in a way does not conform to traditional expectations or disruption of patriarchal frame.  Key words: Female persona, Female auteurs, Nollywood films, Gender misrepresentation, Patriarchal frame